(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Postpartum hemorrhage (PPH) is always one of the leading causes of maternal morbidity and mortality globally. PPH accounts for the most significant share of deaths after vaginal delivery. Latest research indicates that a long duration of labor may be a major factor for PPH, the relationship between the stages of labor and PPH has not been deeply studied. Objective: To evaluate the relationship between the time each stage of labor lasts and the development of postpartum hemorrhage in women having vaginal delivery. Methods: At Jinnah Postgraduate Medical Center (JPMC), a prospective observational study took place from March to May 2025. A total of 300 women who gave birth through vaginal delivery were enrolled in the study. The duration of the first, second, and third stages of labor was determined by partograph recording. Blood loss of ≥500 mL within 24 hours of delivery was considered postpartum hemorrhage. SPSS version 26 software was utilized for data analysis. Chi-square tests and logistic regression were applied to determine associations. Results: PPH was observed in 16% of the patients. The lengthening of the first phase of labor (> 10 hours) was statistically significantly linked to higher PPH risk (p <0.001). The PPH incidence resulted in approximately three times increase when the second stage lasted for more than two hours, it was the extension of the third stage beyond 15 minutes, which was most frequently associated with the hemorrhage (p <0.001). The probability of PPH rose proportionally with the total labor duration at each stage. Conclusion: Extending the length of any phase of labor significantly raises the likelihood of a mother bleeding heavily after a vaginal delivery. Carefully observing each stage and providing prompt obstetric interventions if needed are the key steps towards the reduction of bleeding complications and better maternal outcomes.